Derivation of Load Peak Voltage, Power Consumption and Potential Energy Management in a Thyristor Controlled Marx Impulse Generator for Capacitor Discharge Application - Hojabri, Mojgan; Toudeshki, A.; Mariun, Norman; Nizam, H.; N. I., Abdul Wahab; Y., Ali Sai'd; Saadatian, O.; M., Mansoor; Saadatian, E. (Islamic Azad University, Majlesi Branch, 2013)
Calculation of the load peak voltage, potential energy and power consumption of a Marx impulse generator, as a function of time, are presented. The equations are generalized and can be used to the design of any type of n-stage Marx impulse generator. The results were validated for a thyristor controlled Marx impulse generator with a maximum number of stages of 10 and 3 kV input DC voltage, which used 1 MΩ resistors and 33 nF capacitors in its topology.